Estudio avifaunístico para la elaboración de una guía específica del Cuyabeno River Lodge, ubicado en la Reserva de producción faunística Cuyabeno en la provincia de Sucumbíos. - Cuchiparte Guamangate, Efrain (2017)
Biodiversity is one of the most significant resources for the country; unfortunately, bad management and lack of research to promote its care has resulted in the loss of vegetation coverage producing the reduction of habitats which have become threatened. This project aims to contribute to biodiversity conservation through the profiling of birds species through the registration of individuals for the drafting of a specific guide belonging to the area of influence of the Cuyabeno River Lodge; three goals were proposed to develop this research. Firstly, the current condition of the area was defined through the gathering of information from self-government of the Province (GAD for its acronym in Spanish), interviews and the Ecologic Rapid Assessment (EER for its acronym in Spanish). Once, the ecological and social status of the area of birds was defined, the registration was conducted. It was established two areas for this research; one was the trails (El Ceibo and El Saladero) which was described as linear transects. Along the 2.380 meters that knock into shape it, counting points were defined in the forest clearings. A total of 25 forest clearing points were established. The other area was set as direct observation point at the front area of the Lodge along the river with a total of 100 linear meters. As a result, 33 species were identified: 16 in the Lodge, 16 in El Ceibo Trail and 21 El Saladeroero trail. Those species were taxonomically classified through the Greenfield and Ridgely methodology, by this data, the biodiversity index was calculated through the Margalef method that allowed to compare the different trails to conclude El Saladeroero trail was the one with highest diversity index. Finally, the data collected was used to design and create a bird guide of the Cuyabeno River Lodge. This guide could be utilized as an educational tool to help on the identification of bird species in the Lodge. Besides the research record, the guide could contribute to improve the conservation of ideas to take care of the environment maintaining of habitat for the species and promoting birdwatching giving the possibility to identify them during the tours.